The effect of financial literacy and financial efficacy on individual financial management - Naili Saadah (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2020)
Purpose – This study aims to determine the effect of financial literacy and financial efficacy on financial management.Method – Using mixed methods, namely quantitative and qualitative, this study managed to collect a sample of 307 respondents.Result – This research provides evidence that the level of a person's financial knowledge can affect his financial management as well as his financial satisfaction, with these results directly this research strengthens the evidence that gender does not affect financial management. it's the habits or behaviors that lead someone to act.Implication – This research can be used to understand behavioral financial management in individual level.Originality – Many studies show that a society with good financial literacy will have an impact on the formation of a financially independent society. However, the problem here is that there is still discrimination against women regarding financial management. Basically, whether or not they are able to manage finances is not based on gender but on the behavior of the individual. To strengthen this, research is present to prove that individual behavior which includes the level of financial knowledge and financial satisfaction affects their financial management.